Pengembangan Media Pembelajaran Interaktif Berbasis Teknologi Augment Reality Untuk Meningkatkan Kemampuan Berpikir Kreatif Anak - Ado Tukan, Krisantus Aprieandi; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 11 No 4 (2023): JELIKU Volume 11 No 4, May 2023, 2023)
Augmented Reality (AR) is an audio visual mediain the form of content that can be in the form of 2 dimensions or 3 dimensions placed on physical media where the media is placed. Media is a tool that is useful as a tool to connect the sender and recipient of the message. Meanwhile, learning media is a facility that bridges teaching staff and students in a teaching and learning activity that is useful for providing knowledge, and this process is called a two-way communication process. The media must be involved in this process. With the AR students are expected to think more deeply about the information received. Implementation of teaching and learning activities by utilizing tools in the form of AR able to provide direct benefits in the learning process.tools AR are designed to provide users with more specific information than concrete objects. The function of AR is to visualize an abstract picture in order to provide a more detailed understanding and describe the structure of a specific object model.